Signal processing of C-RTD Sensor output as the input to the instrument of low temperature monitoring using Arduino Uno Rev.3 - Rismawan, Rismawan; Toifur, Moh. (Indonesian Review of Physics (IRiP), 2018)
The C-RTD (Coil-Resistance Temperature Detector) output signal is an analog signal in the form of a direct voltage. This value changes with changes in RTD temperature. This analog signal can be read by users using a multimeter or similar device but does not directly indicate the RTD temperature. In order to obtain RTD temperature values, an additional device is required. In order to have a useful value and practicality, a device that can convert analog signals into values can be read directly by the user. The microcontroller was chosen as a used device. The selected microcontroller system is Arduino Uno because has been coupled with input and output ports so users only need to enter programs related to the system being created. In the other hand Arduino Uno by considering the low cost and practical. For the measurement system, the RTD output signal must be conditioned into a digital signal using the ADC so that it can be processed by the microcontroller. From testing instrument obtained that the system has been able to convert analog RTD signals into digital signals. The range of measurement is -176°C to  0°C with an accuracy of ± 0.20 / mV.